ضمانات استقلال القضاء - صمامه, كمال; تركي, محمد السعيد (University of Eloued جامعة الوادي, 2018)
The Constitution and the law together guarantee the administrative judiciary a set of guarantees, which confirms its independence from the executive authority on the one hand and independence from the ordinary judiciary on the other hand, and this through, The Recognition of an independent administrative judge (organic independence of judges, and functional independence of judges).and Subjecting administrative judges to the Basic Law of the Judiciary. The actual independence of the administrative judiciary was enshrined in the Constitution of 1996, which was radically changed in the existing judicial system. Article 152 of this law affirmed that it establishes the Council of State as a body in charge of the work of administrative judicial bodies. The first is the ordinary judiciary (composed of the courts, the judicial boards and the Supreme Court), the second is the administrative judiciary (which consists of the administrative courts and the Council of State).
الملتقى الدولي الثامن: التوجيهات الحديثة للقضاء الإداري ودوره في إرساء دولة القانون 06-07 مارس 2018 جامعة الوادي
Keywords: القضاء الإداري، إزدواجية القضاء، مجلس الدولة، الإستقلال القضائي; Administrative Judiciary, Judicial Duplication, State Council, Judicial Independence